FAKTOR-FAKTOR YANG MEMPENGARUHI SATURASI OKSIGEN PADA PASIEN POST OPERASI DI RUANG PACU - Rully Annisa; Marta Tania Gabriel Ching Cing; Trias Eka Nurlela (Jurnal Ilmiah Keperawatan IMELDA, 2026)
Background: Oxygen saturation is one of the important parameters in assessing the patient's oxygenation condition, especially during the recovery phase in the Post-Anesthesia Care Unit (PACU). This phase is very crucial because patients who have just undergone anesthesia are at risk of oxygenation disorders due to the effects of anesthesia, surgical procedures, or the patient's physiological condition. Objective: to identify and analyze factors that influence oxygen saturation in post-operative patients in the Post-Anesthesia Care Unit (PACU) and are expected to contribute to improving the quality of post-operative care and preventing serious, potentially life-threatening complications. Method: the data analysis technique uses descriptive analysis, namely presenting the distribution of oxygen saturation data and patient characteristics descriptively in the form of tables or graphs. The sample in this study was post-operative patients in the PACU room of RSI Purwokerto with a total of 62 patients. And using inferential analysis, namely the spearman Rho Test: to examine the relationship between age, gender, smoking status, and blood pressure with oxygen saturation and logistic regression test: to determine the most dominant factor influencing oxygen saturation with n = 62 patients. Results: shows a significant relationship between blood pressure and oxygen saturation, with a correlation coefficient value of 0.742 (very strong relationship category, p <0.05), and in gender, a correlation coefficient value of -0.332 (weak relationship, p <0.05) was obtained, the same as in smoking status showing a correlation coefficient of -0.369 (weak relationship, p <0.05). Conclusion: blood pressure, gender, and smoking status factors are related to oxygen saturation in postoperative patients. Suggestion: for further researchers, it is hoped that they will conduct research in various scopes, for example peri-operative.